2012
DOI: 10.1002/tea.21034
|View full text |Cite
|
Sign up to set email alerts
|

Lesson study for accessible science: Building expertise to improve practice in inclusive science classrooms

Abstract: The Lesson Study for Accessible Science (LSAS) project created middle school teams comprised of both science and special education teachers who engaged in collaborative work to improve instruction in inclusive classrooms. The intervention is based on Lesson Study, a professional development approach that originated in Japan, which supports the systematic examination of practice and student understanding. Using an experimental design, teams of teachers were randomly assigned to the LSAS intervention or to a wai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 37 publications
1
53
0
1
Order By: Relevance
“…In-service and pre-service teachers from different disciplines, including history, language arts, math, science, and social studies, have made effective use of the process (Blum et al 2005;Marble 2006;Ogden et al 2008;Rock and Wilson 2005;Sibbald 2009). Specific to science, educators engaged in lesson study have been shown to be effective in developing and implementing science lessons (Marble 2006;Mutch-Jones et al 2012). Furthermore, lesson study exhibits certain characteristics of effective professional development in science as outlined in the literature (e.g., Guskey and Yoon 2009;Loucks-Horsley et al 2003;Penuel et al 2007): It occurs within authentic contexts over an extended duration; it fosters communication among…”
Section: The Lesson Study Approachmentioning
confidence: 98%
“…In-service and pre-service teachers from different disciplines, including history, language arts, math, science, and social studies, have made effective use of the process (Blum et al 2005;Marble 2006;Ogden et al 2008;Rock and Wilson 2005;Sibbald 2009). Specific to science, educators engaged in lesson study have been shown to be effective in developing and implementing science lessons (Marble 2006;Mutch-Jones et al 2012). Furthermore, lesson study exhibits certain characteristics of effective professional development in science as outlined in the literature (e.g., Guskey and Yoon 2009;Loucks-Horsley et al 2003;Penuel et al 2007): It occurs within authentic contexts over an extended duration; it fosters communication among…”
Section: The Lesson Study Approachmentioning
confidence: 98%
“…The majority of studies looking at interventions to teach science content for students with moderate and severe intellectual disabilities have focused on direct instruction and an emphasis on science vocabulary (Jimenez, Browder, Spooner, & Warren, ). The inquiry approaches and level of deeper exploration of concepts by the NGSS require critical thinking, reasoning skills, skills of argumentation and communication, as well as the ability for students to explore abstract concepts, a challenge for most students with intellectual disabilities (Mutch‐Jones, Puttick, & Minner, ; NRC, ).…”
Section: Science In Special Educationmentioning
confidence: 99%
“…Integral to the lesson study process is "the belief that discussing others' points of view enhances the learning process and the final product" (Loucks-Horsley et al 2003). Although relatively new to the United States (Wiburg and Brown 2007), lesson study has been shown to have positive effects on classroom educators' knowledge, skills and confidence (Rock and Wilson 2005;Wiburg and Brown 2007) and their abilities to design and teach science lessons (Marble 2006;Mutch-Jones et al 2012).…”
Section: Communities Of Practicementioning
confidence: 99%